Transnational same-sex couples: negotiating intimacy and home(s) ‘here’ and ‘there’ - Anzola Beltran, Juan Diego (2018)
This thesis explores the ways in which transnational same-sex couples construe and experience transnational migration, intimacy, and home. The study was initially born out of the need to contribute to the young, but growing body of scholarly work in relation to queer migration studies. For long, the figure of ‘the migrant’ was founded on heterosexual terms only, thus impeding any possibility of exploring the lives of those with non-normative gender and sexual identities. During the last two decades or so, new scholarship has tried to alter this picture, arguing for a more inclusive assessment of global migration. This project aims to further the scholarly conversations in this regard, but it also wishes to go beyond the traditional economic and political spheres in which the migrant is usually placed in; hence, it promotes a study of migration that is also preoccupied with the intimate and emotional life of LGBT+/queer migrants.